2018
DOI: 10.1038/s41598-018-35576-0
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged systemic hyperglycemia does not cause pericyte loss and permeability at the mouse blood-brain barrier

Abstract: Diabetes mellitus is associated with cognitive impairment and various central nervous system pathologies such as stroke, vascular dementia, or Alzheimer’s disease. The exact pathophysiology of these conditions is poorly understood. Recent reports suggest that hyperglycemia causes cerebral microcirculation pathology and blood-brain barrier (BBB) dysfunction and leakage. The majority of these reports, however, are based on methods including in vitro BBB modeling or streptozotocin-induced diabetes in rodents, ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
0
19
1
1
Order By: Relevance
“…Our results also reveal shortcomings in the classical retinal digest assay that has been cited as support for pericyte drop-out in diabetic conditions 20 , and they suggest that pericyte loss as a causative factor in diabetic vasculopathies needs to be reexamined, as it has already in the Akita mouse model 11 . Our analysis of immunostained retinas revealed that up to 50% of all pericyte somas were associated with a basement membrane bridge (combination of pericyte bridges and basement membrane bridged pericytes), which would have been miscounted as endothelial somas 47,48 in the retinal digest assay and potentially accounts for the approximately 30% 20 loss in pericyte density observed with this assay in diabetes and Ang2 stimulation.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Our results also reveal shortcomings in the classical retinal digest assay that has been cited as support for pericyte drop-out in diabetic conditions 20 , and they suggest that pericyte loss as a causative factor in diabetic vasculopathies needs to be reexamined, as it has already in the Akita mouse model 11 . Our analysis of immunostained retinas revealed that up to 50% of all pericyte somas were associated with a basement membrane bridge (combination of pericyte bridges and basement membrane bridged pericytes), which would have been miscounted as endothelial somas 47,48 in the retinal digest assay and potentially accounts for the approximately 30% 20 loss in pericyte density observed with this assay in diabetes and Ang2 stimulation.…”
Section: Discussionmentioning
confidence: 67%
“…This rapid change in pericyte bridges was recapitulated by injection of recombinant Ang2 and PDGF-BB, both of which are cytokines upregulated in diabetes 20,21 . Elevation of pericyte bridges in Akita mice 11 provides further evidence that high blood sugar could be a short-term stimulus for enrichment of this pericyte phenotype.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…One hypothesis is that these pericyte-like bridges form as a result of pericyte detachment (9)(10)(11)(12), where it is assumed that a fully attached pericyte migrates (or begins to migrate) away from the capillary on which it resides and extends cell processes or its entire cell soma to form a bridge from one capillary to another. Alternatively, other cell types may potentially give rise to these bridging cells or contribute to these basement membrane bridges (8).…”
mentioning
confidence: 99%